Boosting Immunity of the Registered Reports System in Psychology to the Pandemic - Sasaki, Kyoshiro; Yamada, Yuki (Frontiers in Research Metrics and Analytics, 2020)
In psychology, a Registered Reports system is key to preventing questionable research practices. Under this system, manuscripts, including their detailed protocols (i.e., hypothesis, experimental design, sample size, and methods of statistical analysis), are reviewed prior to data collection. If a protocol manuscript is accepted, publication of the full manuscript including the results and discussion is guaranteed in principle regardless of whether the collected data support the registered hypothesis. However, this assurance of publication might be broken under the impact of the COVID-19 pandemic: Begrudging withdrawal of an accepted protocol manuscript due to a difficulty to meet the deadline by compelling reasons (e.g., pandemic) has occurred. The present paper reports the first author’s real-life experience related to the collapse of the assurance of publication in the Registered Reports system and discusses the disbenefits of this collapse. Furthermore, we propose the implementation of a journal section specific to protocol manuscripts as a solution to the crisis of the Registered Reports system.